The king is coming : it's time to prepare for the return of Christ - Bevere, John (W Publishing, 2026)
If Jesus were to return tomorrow, would you be ready? In The King Is Coming, John Bevere discusses why the Second Coming is both relevant and critical for the Christian faith. Other than salvation, it's the second most discussed topic both in the New Testament and by early church fathers in the first three centuries. More than a book about prophecy, this life-changing guide will help believers live fully prepared for Christ's return while transforming the way we love, serve, and glorify God.